Menstrual and Reproductive Factors, Hormone Use, and Risk of Pancreatic Cancer: Analysis From the International Pancreatic Cancer Case-Control Consortium (PanC4) - Lujan-Barroso, Leila; Zhang, Wei; Olson, Sara H; Gao, Yu-Tang; Yu, Herbert; Baghurst, Peter A; Bracci, Paige M; Bueno-de-Mesquita, H Bas; Foretová, Lenka; Gallinger, Steven; Holcatova, Ivana; Janout, Vladimír; et al. (Pancreas, 2016)
OBJECTIVES: We aimed to evaluate the relation between menstrual and reproductive factors, exogenous hormones, and risk of pancreatic cancer (PC). METHODS: Eleven case-control studies within the International Pancreatic Cancer Case-control Consortium took part in the present study, including in total 2838 case and 4748 control women. Pooled estimates of odds ratios (ORs) and their 95% confidence intervals (CIs) were calculated using a 2-step logistic regression model and adjusting for relevant covariates. RESULTS: An inverse OR was observed in women who reported having had hysterectomy (ORyesvs.no, 0.78; 95% CI, 0.67-0.91), remaining significant in postmenopausal women and never-smoking women, adjusted for potential PC confounders. A mutually adjusted model with the joint effect for hormone replacement therapy (HRT) and hysterectomy showed significant inverse associations with PC in women who reported having had hysterectomy with HRT use (OR, 0.64; 95% CI, 0.48-0.84). CONCLUSIONS: Our large pooled analysis suggests that women who have had a hysterectomy may have reduced risk of PC. However, we cannot rule out that the reduced risk could be due to factors or indications for having had a hysterectomy. Further investigation of risk according to HRT use and reason for hysterectomy may be necessary.
Keywords: Logistic Models; rizikové faktory; Pancreatic Neoplasms; logistické modely; Odds Ratio; Case-Control Studies; lidé; Female; ženské pohlaví; studie případů a kontrol; Risk Factors; odds ratio; Humans; nádory slinivky břišní